Gender and space : femininity, sexualization, and the female body - Sīmantinī (Sage Publications, 2001)
Straddling the domains of anthropology and gender studies, this book deals centrally with the conjunction of space and gender in practices and discourses of femininity and sexuality. Drawing on fieldwork by resisting a monograhic format, it weaves together conceptual and ethnographic narratives in elaborating a theory of gender and space. The chapters include accounts of the domains and activities of women, cultuaral perceptions and experiences of the female body, exploration of gender and ritual realm as well as suggestions for formulating a ground for female agency within a body-space matrix.